Interpersonal Meaning in the Gettysburg Address (Systemic Functional Analysis) - Andi Risang Qinthar Latunra (Hasanuddin University, 2022)
This study aims to uncover the types of mood and modality used in the Gettysburg Address and how Abraham Lincoln uses them to give dedication and emphasize the struggle to achieve union and equality. This study employed descriptive qualitative research design in analyzing the data. the data were collected from the text of the Gettysburg Address. After the data were collected, they were categorized into their proper interpersonal meaning elements classification. Then, the writer determined whether the data are in declarative mood, imperative mood, or interrogative mood, and revealed the type, orientation, and value of the modalities. Finally, the writer explained the mood and modality used by the speaker to give dedication and emphasize the struggle to achieve union and equality. The result shows that declarative mood occurs the most compared to the imperative mood. By using declarative mood, the speaker explains that they are struggling to win the war, they are going to give dedication for the fallen soldiers, and they are continuing their unfinished work to achieve union and equality. Meanwhile, the speaker uses imperative mood to command the listener that they must dedicate a portion of the aftermath field for their fallen soldiers who struggled to achieve union and equality. In using modality, the speaker positions their messages in the degree of Probability, Obligation, Inclination, and usuality. Most of them are in a high value and the rest are in median and low value.